piwi encodes a nucleoplasmic factor whose activity modulates the number and division rate of germline stem cells. - Cox, D.N.; Chao, A.; Lin, H. (Development, 2000)
piwi represents the first class of genes known to be required for stem cell self-renewal in diverse organisms. In the Drosophila ovary, piwi is required in somatic signaling cells to maintain germline stem cells. Here we show that piwi encodes a novel nucleoplasmic protein present in both somatic and germline cells, with the highly conserved C-terminal region essential for its function. Removing PIWI protein from single germline stem cells significantly decreases the rate of their division. This suggests that PIWI has a second role as a cell-autonomous promoter of germline stem cell division. Consistent with its dual function, over-expression of piwi in somatic cells causes an increase both in the number of germline stem cells and the rate of their division. Thus, PIWI is a key regulator of stem cell division - its somatic expression modulates the number of germline stem cells and the rate of their division, while its germline expression also contributes to promoting stem cell division in a cell-autonomous manner.